Aquatic photochemical kinetics of benzotriazole and structurally related compounds. Issue 5 (27th March 2015) - Janssen, Elisabeth M. L.; Marron, Emily; McNeill, Kristopher
Abstract : Benzotriazole corrosion inhibitors are not completely removed during wastewater treatment and are frequently detected in surface waters. Abstract : Benzotriazole corrosion inhibitors are not completely removed during wastewater treatment and are frequently detected in surface waters. Here, the photochemical kinetics of benzotriazoles and structurally related compounds were assessed for natural aqueous environments. The direct photochemical half-lives during exposure to simulated sunlight ranged from 1.3 to 1.8 days for benzotriazole and its derivatives (4-methyl-, 5-methyl-, 4-hydroxy-substituted benzotriazoles). Benzotriazole is more resistant to direct photodegradation than indazole (0.28 days) and indole (0.09 days), while benzimidazole showed no significant decay. Hydroxyl radicals (1.6 × 10 −16 M) and singlet oxygen (2.5 × 10 −13 M) are formed during simulated sunlight exposure in the presence of dissolved organic matter (13 mgC L −1 ). All tested compounds reacted rapidly with hydroxyl radicals near the diffusion-controlled limit (8.3 to 12 × 10 9 M −1 s −1 ). Only 4-hydroxybenzotriazole and indole showed significant reactivity towards singlet oxygen and their photochemical half-lives in the presence of organic matter were shorter (0.1 days for both) than for benzotriazole and its methylated derivatives (1.4–1.5 days). The photochemical half-lives determined here are relatively long and support the persistence of benzotriazoles in the environment. At the same time, these results suggest that photochemical transformation can be supplementary to microbial degradation. While the presented study focused on environmental photodegradation kinetics, the relevance of transformation products remains to be investigated.